In the Name of Identity: Online Campaigning in Provincial Administrative Organization Elections in Thailand’s Three Southern Border Provinces - Tuansiri, Ekkarin (Journal of Social Sciences Naresuan University, 2026)
The 2025 Provincial Administrative Organization (PAO) elections in Thailand’s southern border provinces reflected the dynamic convergence of identity politics and political marketing. This research aims to examine the use of Malayu-Islamic identity in electoral campaigning, focusing on the analysis of the official Facebook pages of PAO candidates in Yala, Pattani, and Narathiwat provinces, where social media has become the primary platform for political communication. The study findings reveal that many candidates utilized Malayu-Islamic identity as political capital through image construction, language use, references to religious activities, and emphasis on being Malayu-Muslim figures having intimacy with the community. Simultaneously, political marketing strategies were employed in conjunction, particularly message framing and targeting, to create distinctive political brands that appealed to different voter groups. The analysis demonstrates that Facebook pages served not merely as publicity channels, but also as identity-based battlegrounds where identity became a political commodity that was negotiated, materialized, and repeatedly reproduced throughout the campaigning process. These findings indicate that local politics in the southern border provinces in 2025 encompassed more than just competition over policies or resources, but also represented a contest to define the meaning of being Malayu through digital spaces. This was particularly evident in the use of local identity as a communication tool, encompassing both policies connected to local Malayu identity and broader political discourse.